Research on the health status and influencing factors of the older adult floating population in Shanghai - Wu, Lianxia; Li, Wei; Wang, Shaogu; Weihua, Guan; Wang, Xianyu (Frontiers in Public Health, 2024)
Over the past decade, against the dual background of population aging and mobility, the elderly floating population has become a new type of mobile group in China, continually congregating in large cities, posing significant challenges to the socio-economic development, eldercare services, and public management of these metropolises. Shanghai, as a mega-city and the economic center of the China, is typically representative of the national population. This research, based on the dynamic monitoring data of Shanghai's migrant population in 2018 and employing mathematical statistics and binary Logistic regression models, analyzes the demographic characteristics and health status of the elderly floating population in Shanghai in the new era and reveals its primary influencing factors. The research found: (1) A prominent contradiction in the scale and structure of the elderly floating population, with widowed and low-educated mobile elderly requiring attention. (2) There is a lack of health knowledge, and the proportion of local reimbursement is low. Over 90% of migrant elderly self-assessed their health (with a very few unable to care for themselves), far higher than the proportion of elderly who are not sick (injured) or uncomfortable (actually healthy), which exceeds 70%. The health status of migrant elderly deteriorates with age, and those who have never attended school and live alone have the worst health status. (3) Elderly people with advanced age and low educational levels are at risk of health issues, while a better living environment can reduce the risk of illness in the elderly floating population. Low family income, poor housing affordability, and the medical burden brought about by illness can easily lead to elderly floating populations falling into the trap of elderly poverty, and elderly people from central regions and those who migrate along have difficulty adapting to city life, leading to poor self-assessed health. Meanwhile, community/enterprise health education helps to enhance the health protection awareness of the elderly floating population. Finally, based on the governance concept of "mobility publicness," several public management and service optimization strategies for social support for the elderly floating population in Shanghai are proposed.